2007
DOI: 10.1177/0193945907303102
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Condom Use Among Sexually Experienced Latino Adolescents

Abstract: There is limited research on how aspects of Latino culture affect condom use among Latino adolescents. In this study, the authors examined the effects of familialism, gender roles, and religiosity on condom use intentions and past condom use. Results showed only religiosity predicted past condom use; no other cultural variable had either a direct or an indirect effect on condom use intentions or past condom use. These findings represent an important effort in promoting safer sex behaviors among sexually active… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 26 publications
1
57
0
Order By: Relevance
“…Miller and Gur (2002) observed that highly religious girls had lower avoidance and refusal skills compared to less religious and nonreligious peers, possibly explaining Latinas' higher rate of sexual activity. The Catholic Church's prohibition of birth control (Fuller, 1996) may help explain low rates of condom use among Latinas (Martin et al, 2011), although several researchers exploring religiosity and condom use found either no direct effect (Baumeister, Flores, & Marín, 1995;Peragallo, 1996;Unger & Molina, 1999) or found religiosity benefited males but not females (Villarruel, Jemmott, Jemmott, & Ronis, 2007).…”
Section: Religiosity and Risky Sexual Behaviormentioning
confidence: 99%
“…Miller and Gur (2002) observed that highly religious girls had lower avoidance and refusal skills compared to less religious and nonreligious peers, possibly explaining Latinas' higher rate of sexual activity. The Catholic Church's prohibition of birth control (Fuller, 1996) may help explain low rates of condom use among Latinas (Martin et al, 2011), although several researchers exploring religiosity and condom use found either no direct effect (Baumeister, Flores, & Marín, 1995;Peragallo, 1996;Unger & Molina, 1999) or found religiosity benefited males but not females (Villarruel, Jemmott, Jemmott, & Ronis, 2007).…”
Section: Religiosity and Risky Sexual Behaviormentioning
confidence: 99%
“…Increased religiosity (including religious attendance and prayer/meditation) has been associated with delayed sexual intercourse initiation (Halpern, Waller, Spriggs, & Hallfors, 2006), fewer number of sexual partners (Weeden, Cohen, & Kenrick, 2008) and less pre-marital sexual activity (Barkan, 2006;1031Mental Health, Religion & Culture Bryant et al, 2003. Some research suggests that this relationship is stronger for females (Rostosky, Wilcox, Wright, & Randall, 2004;Vazsonyi & Jenkins, 2010) and differ based on ethnic group (McCree, Wingood, DiClemente, Davies, & Harrington, 2003;Villarruel, Jemmott, Jemmott, & Ronis, 2007).…”
Section: Religious Behaviours and Health Behavioursmentioning
confidence: 99%
“…We do not have information about how these three measures map to culturally defined gender roles (such as marianismo or machismo), religiosity, familialism, or other important Hispanic cultural norms [8,36] that may directly influence reproductive and sexual behavior. Neither do we Table 4 Statistically significant odds ratios and 95% confidence intervals associated with the interaction of gender with generation and country of origin,a among the full Hispanic sample, weighted, National have contextual information from the society of origin, the new settlement society, or the immigration history, which may also shape adolescent reproductive health and behavior.…”
Section: Study Strengths and Weaknessesmentioning
confidence: 99%